Salvage after Retroperitoneal Kidney Allograft Torsion - Justin M. Greco; David C. Mulligan; Peter S. Yoo (Case Reports in Transplantation)
Torsion of a transplanted kidney into the retroperitoneal space is a rare occurrence, with only three other reported cases. Failure after kidney transplantation is caused by surgical, immunological, and infective complications. Torsion is a complication that poses a serious risk of ischemic graft failure, and, if suspected, sonographic evaluation helps ascertain the diagnosis. Here, we present the case of a 69-year-old transplant recipient whose routine postoperative ultrasound confirmed vessel patency, however subsequently developed clinical signs of renal allograft compromise. Repeat ultrasound showed signs of vascular compromise and the patient was emergently re-explored. Torsion of the renal allograft about its pedicle was encountered and corrected by manual detorsion and nephropexy to the retroperitoneal wall. Clinicians should recognize pedicle torsion as a potential cause of renal allograft failure and the role of nephropexy in its management.